The Measurement Of Service Quality With SERVQUAL For Different Domestic Airline Firms In Turkey - Kenan, Aydın; Yıldırım, Seda (Serbian Journal of Management, 2012)
The primary purpose of this research is to determine whether there is a significant difference between the passengers’ service quality expectations and service quality perceptions in different airline firms. The collateral purpose is to find out whether there is a significant difference between service quality expectation and service quality perception of the passengers who have different socio-demographic characteristics. To achieve these purposes, the 5 - dimensional scale, suggested by Parasuraman et.al (1988) was applied to the airline travel sector. The questionnaire was used in interviewing the passengers at Sabiha Gokcen Airport in Istanbul in Turkey with a “face to face” method. The data was analysed in SPSS 16 program after questionnnaires were collected. Firstly, the demographic characteristics of passengers were presented for different airline firms. Then the highest and the lowest gaps for the each statement was determined. Lastly it was compared if there was a significant difference between the service quality expectation and perception for different domestic airline firms.